Plane trigonometry - Fuller, Gordon (New York : McGraw Hill Education, 1959)
This book has been prepared as a first course in plane trigonometry for college students who need a sufficient mastery of the subject for its employment in more advanced mathematics and in various fields of science.
Chapter 1. Angles -- Chapter 2. The trigonometric functions -- Chapter 3. Approximate numbers and tables of trigonometric functions -- Chapter 4. Applications to right triangles -- Chapter 5. Fundamental identities -- Chapter 6. Trigonometric functions of several angles.
Includes index.
Keywords: PLANE TRIGONOMETRY